Implementation Gap: Realization of Coastal Community Empowerment Program in the Era of the Covid-19 Pandemic, Johan Pahlawan District, West Aceh Regency - Safrida Safrida; Desi Maulida; Nila Safrida (Jurnal Borneo Administrator: Media Pengembangan Paradigma dan Gaya Baru Manajemen Pemerintahan Daerah, 2022)
The Covid-19 pandemic has caused chaos in the living order of the world community, including Indonesia. As a maritime country with a high population in coastal areas, the pandemic has caused the economic stability of fishermen to decrease drastically, so solutions are needed in the form of empowerment programs not to cause greater problems. This study aims to find the implementation of the coastal community empowerment program carried out by the government in the era of the Covid-19 pandemic, Johan Pahlawan District, West Aceh Regency, which is the centre of fisheries and marine management locations in the Regency. The research method that the author uses is descriptive qualitative. The results found through this research are that the government's empowerment during the pandemic is mostly only in the form of financial assistance. They even realize the aid funds provided to fishermen groups are still not on target. Therefore, this study concludes that implementing the coastal community empowerment program by the government remains inappropriate and unsuccessful in overcoming the problems faced by fishermen back from the past to the current Covid-19 pandemic. Thus, the government must prioritize the community's needs by improving the management of fishermen's businesses, such as forming cooperatives and increasing cooperation with partners, which are the main aspects of improvement to improve the fishermen's standard of living